An Analisis Kemampuan Pemecahan Masalah Matematika Siswa Berdasarkan Langkah Polya - Alawiyah, Titi Nur; Sridana, Nyoman; Kurniawan, Eka; Hayati, Laila (FKIP Universitas Mataram, 2024)
This research describes mathematical problem-solving abilities based on Polya's steps. This type of research is qualitative descriptive research with data collection techniques: tests, interviews, and documentation. The subjects selected were 6 students based on test results and divided into 3 groups, each consisting of 2 students with high, medium, and low mathematical problem-solving abilities who were then interviewed. The data analysis technique used is the Miles & Huberman model with the following steps: data collection, reduction, data presentation, and conclusion. The results of data analysis show that students' problem-solving abilities are: 1) high category, able to understand the problem, able to plan a solution, able to carry out the solution plan even if there is a slight error in calculations, and able to look back at the results; 2) medium category, able to understand the problem, less able to plan a solution, less able to implement the resolution plan and less able to review the results; 3) low category, less able to understand the problem, unable to plan a solution, unable to implement the resolution plan and unable to look back at the results obtained.